(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article reveals the ways, methods of organizing primary education in the context of informatization of education and the principles of designing a modern lesson in primary education. Their relationship and method of implementation are determined, the importance of the concept of the theory of educational activity in the design of a modern lesson in elementary education is based. Following these principles, the relevance of the design of a modern lesson in primary education and the requirements for it are listed.